(untitled) (Research, Society and Development, 2022)
COVID-19 was categorized as a pandemic in March 2020 and is manifested by mild respiratory symptoms although there is a possibility of worsening and death. The causes of death have been associated with thrombotic processes and activation of coagulation with exacerbated inflammatory reaction. Thus, the present study aimed to investigate tests of the inflammatory profile, C Reactive Protein (CRP), and of the thrombotic profile, D-dimer (DD), Prothrombin Time (PT), International Normalized Ratio (INR) and Activated Partial Thromboplastin Time (TTPa), as prognostic markers in patients with COVID-19 in their different outcomes. The work consists of an analysis of tests from patients admitted with outcome discharge and death, with positive molecular test for SARS-CoV-2, between March 2020 and January 2021, belonging to the COVID-19 Data Sharing/BR repository of the Hospital Beneficência Portuguesa, using the Mann-Whitney two-tailed test and Bonferroni correction. In the death group, 97.7% of the patients had a CRP above normality and 100% had a DD above the reference. The PT, in the discharge group, was above normal in 36.21% of the patients, while in the death group, it was 82.8%. The TTPa, in the discharge outcome, was above normal in 14.8% of the patients, on the other hand, 54.54% at death. In all tests evaluated, the medians of the death group were higher than the discharge group. Although the sample was from a single hospital, important trends were observed. CRP and DD can be used as prognostic markers for COVID-19 and PT, INR and TTPa, although showing relevant results, need further investigation.